Analisis Kondisi Sosial Ekonomi Penerima Bantuan Kartu Keluarga Sejahtera di Nagari Pilubang Kecamatan Sungai Limau Kabupaten Padang Pariaman - Rahayu, Putri; Mariya, Sri (Lembaga Yasin AlSys, 2026)
This study is motivated by the limited research on the socioeconomic conditions of recipients of the Kartu Keluarga Sejahtera (KKS; Prosperous Family Card) in Nagari Pilubang, Sungai Limau District, Padang Pariaman Regency, despite the significant implications of this phenomenon for the effectiveness of KKS as an instrument of poverty alleviation. The study aims to describe the conditions of income, fulfillment of basic needs, health, and education among KKS beneficiary households in Nagari Pilubang. A descriptive quantitative design was employed with a population comprising all 691 KKS recipients, from which a sample of 87 respondents was determined using the Slovin formula and selected through proportional random sampling. Data were collected through questionnaires and documentation and analyzed using percentage techniques. The findings show that, in terms of income, household income levels of KKS recipients do not yet meet the expected criteria, although the types of employment of heads of households are in accordance with the categories stipulated by the program. The fulfillment of basic needs is considered to meet the criteria, as indicated by housing conditions (home ownership status, wall type, floor type, and water sources), clothing (purchase of clothing at least once a year), and food consumption (animal protein intake dominated by fish). Health conditions are also deemed to meet the criteria because most community members utilize primary health care (puskesmas) services through government-subsidized BPJS health insurance. In terms of education, the conditions of KKS recipients are aligned with program criteria, as the last educational level of heads of households and mothers is generally completed primary school or no schooling. Overall, the results indicate that although KKS recipients remain in the low-income category, their basic needs fulfillment, access to health services, and minimum educational conditions are consistent with KKS eligibility criteria, thereby providing input for local governments to improve targeting policies and design family empowerment programs for beneficiary households.